Violação constitucional em matéria de tributo e a admissibilidade do recurso extraordinário: entre superposições competenciais e vácuos jurisdicionais - Fernandes, Pablo Gurgel (2020)
This thesis aims to connote some classes of judicial discussions in which the vertical compatibility of at least one criterion of matrix-norm of tax incidence, or of the respective concrete and individual tax norm, will exhibit suitable to be appreciated in the context of incidental constitutionality control by the Brazilian Supreme Court, for not being mere indirect violation for the constitutional block. In other words, this study seeks to specify some requirements that have to guide the identification of an unconstitutional taxation, for the admissibility of the extraordinary appeal filed before the Brazilian Constitutional Court. It will use bibliographic and documentary qualitative research, guided by the combination of hypothetical-deductive and hermeneutic-analytical methods